Large company perspective on hosting idea competitions for start-ups : Speeding up innovation through crowdsourcing - Pöllänen, Taru (fi=Turun yliopisto|en=University of Turku|, 2018)
The ways in which large companies are developing new products has changed in the past years. The new product development process no longer takes place solely inside the company’s boundaries - competitors, customers and smaller companies have been incorporated into the process. This study focuses on idea competitions, a way for large companies to gather ideas and scan multiple start-ups simultaneously. The purpose of the study is to research how large Finnish companies perceive idea competitions for product development in cooperation with start-ups. Furthermore, this study aims to provide best practices for those looking to host an idea competition of their own. A qualitative research approach was chosen to study idea competitions. The data was collected by conducting semi-structured interviews with representatives of companies that had held an idea competition of their own. The theoretical framework of this study, which the interviews were based on, was built-up from previous studies on open innovation, crowdsourcing and idea competitions. It appears that idea competitions are a cost-efficient way for companies to gather new ideas and seek for new partners. The empirical finding of the study indicate that idea competitions can provide the host with both high-quality and several new ideas. Other benefits of hosting competitions were in relation to corporate reputation and corporate social responsibility. In order to host a successful competition, focus needs to be placed on task setting. Additionally, the importance of honesty, good communications and alignment of expectations were seen as requirements for fruitful partnerships to emerge from idea competitions. Hosting together with an intermediary can help companies overcome barriers as they have expertise on the subject and lessen the amount of tied resources pre-competition.